Strategy to increase revenue from transfer of motor vehicle title fees in North Sulawesi province - Marvil G. Parengkuan; Rossy Lambelanova; Sutiyo Sutiyo (Sean Institute, 2024)
North Sulawesi Province implements regional autonomy to provide broader policies and authority to regional governments in managing local affairs. Motor Vehicle Name Transfer Fee (BBNKB) is an important source of income for local governments. Revenue from BBNKB is used to finance various development programs and public services in the region. However, in recent years BBNKB revenues at the Bapenda of North Sulawesi Province have decreased.This research aims to determine and analyze the factors that influence BBNKB revenue at the Regional Revenue Agency of North Sulawesi Province which has not met the target, and to formulate appropriate strategies to increase BBNKB revenue. Data collection was carried out by observation, interviews and documentation. Data analysis was carried out in the stages of data reduction, data presentation and conclusions. The research method used is descriptive qualitative. The theory used is Bryson's Strategic Management (2016) and SWOT analysis by Rangkuti (2014), which is then combined with a litmus test by Bryson, (2016). The research results show that the factors that influence BBNKB receipts involve a reduction in the rate of Transfer of Title Fee for first-delivered Motor Vehicles, a decrease in people's purchasing power, and delays in payment of Transfer of Title Fees for first-delivered Motor Vehicles. Then the formulation of the recommended strategy to increase BBNKB revenues includes a strategy to increase the rate of transfer of title for motorized vehicles for the first delivery, a strategy for creating a system or application for reporting vehicles that have been sold or progressively online and a strategy for collaborating with automotive dealers to help promote new vehicles.